Guided tissue regeneration in peri-radicular surgery - Gabriele Baniulyte; Lorna Burns; Kamran Ali (Elsevier, 2022)
Guided tissue regeneration techniques have been available in dentistry for decades. Primarily used for periodontal surgery and implant placement, their usefulness in periapical surgery has been getting increased attention. From the currently available evidence, guided tissue regeneration can improve patient outcomes. As a result, this technique might become more common in the future. Therefore, this review outlines the main uses of guided tissue regeneration and provides a brief summary of evidence surrounding it, with particular focus on periapical surgery.